2014
DOI: 10.1016/j.ctrv.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation in cancer patients: The global framework

Abstract: Cancer treatment is the most frequent cause of reduced fertility in cancer patients, with up to 80% of survivors affected. None of the established or experimental fertility preservation methods can assure parenthood; instead it may provide a future opportunity to overcome treatment induced sterility. Previous research demonstrated that fertility counselling has clinical and psychological benefit. Therefore, such patient services are recommended by internationally recognized guidelines. Around 70-75% of young c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 65 publications
(83 reference statements)
2
51
0
1
Order By: Relevance
“…For these biologic reasons, a younger age at radiotherapy seems to protect ovarian function in girls receiving BMT. To simulate a prepubertal hormonal milieu, the administration of gonadotropin-releasing hormone analogues before oncologic treatment of childhood cancer has been proposed as a fertility preservation method (4,5). Although we have no data on this type of treatment, a panel of experts of American Society of Clinical Oncology, after reviewing the data in the literature, recently suggested that gonadotropin-releasing hormone analogues are not an effective method of fertility preservation and that these agents should not be relied on to preserve fertility (27).…”
Section: Figurementioning
confidence: 99%
“…For these biologic reasons, a younger age at radiotherapy seems to protect ovarian function in girls receiving BMT. To simulate a prepubertal hormonal milieu, the administration of gonadotropin-releasing hormone analogues before oncologic treatment of childhood cancer has been proposed as a fertility preservation method (4,5). Although we have no data on this type of treatment, a panel of experts of American Society of Clinical Oncology, after reviewing the data in the literature, recently suggested that gonadotropin-releasing hormone analogues are not an effective method of fertility preservation and that these agents should not be relied on to preserve fertility (27).…”
Section: Figurementioning
confidence: 99%
“…Linkeviciute et al, 62 Review N = 71 publications Most young cancer survivors desire parenthood. Providing fertility preservations offers these patients a chance to overcome sterility associated with cancer treatment.…”
Section: International Society For Fertility Preservationmentioning
confidence: 99%
“…For instance, the lack of an integrated referral system, limited resources or oncofertility specialists to refer patients, and time constraints in early cancer treatment consultations have been identified as possible barriers to timely referrals. 14,20,21,28,43,57,58,61,62 Few institutions have been able to demonstrate a standardized referral process to fertility services for adolescent cancer patients. Institutional policies and appropriate referral to a specialist will help alleviate the concerns oncology providers have expressed in addressing fertility with their AYA patients.…”
Section: Practice Guidance For Fertility Preservationmentioning
confidence: 99%
“…Because up to 80% of cancer survivors are at risk for treatment-related infertility, 10 in recent years, national guidelines in many countries have mandated fertility risk assessment and referral for newly diagnosed cancer patients. These include the American Society of Clinical Oncology (ASCO), who published guidelines in 2006 and updated them in 2013, 1 the National Comprehensive Cancer Network (NCCN), 2 the American Society of Reproductive Medicine, the European Society for Medical Oncology, and the European Society of Breast Cancer Specialists.…”
Section: Guidelines For Counseling Newly Diagnosed Cancer Patients Abmentioning
confidence: 99%
“…These include the American Society of Clinical Oncology (ASCO), who published guidelines in 2006 and updated them in 2013, 1 the National Comprehensive Cancer Network (NCCN), 2 the American Society of Reproductive Medicine, the European Society for Medical Oncology, and the European Society of Breast Cancer Specialists. 10 Per NCCN Clinical Practice Guidelines in Oncology (NCCN Guidelines ® ), 2 providers should discuss FP with all eligible patients prior to start of cancer therapy and consider involving a mental health professional to aid in decisionmaking and facilitate coping with the combined threats of infertility and a new cancer diagnosis. Patients interested in preserving fertility should be referred to a specialist within 24 hours.…”
Section: Guidelines For Counseling Newly Diagnosed Cancer Patients Abmentioning
confidence: 99%